Managing commute traffic : from parking provision with ride-sourcing to work hours arrangements considering household travels - Su, Qida (2019)
The traffic mobility in peak hours has always been a challenge in city management. Due to the ubiquitous jobs-housing separation in most metropolitans, commuters inevitably need to travel between home and workplace with decision makings on the travel modes, departure time as well as the work schedule. This thesis then focuses on the commuting behavior and explores the management of morning commute problem from the supply of transportation facilities including parking spaces and ride-sourcing fleet size, to the travel demand of commuters with various work schedules and composite trip purposes.